An Unusual Presentation of Ochronosis with Palmar Pigmentation - Mohan Rao Nandam; Shanthi Vissa; Syam Sundara Rao Byna; Bhavana Grandhi; Sujitha Raguraman (Journal of Clinical and Diagnostic Research, 2019)
Ochronosis is the deposition of homogentisic acid in connective tissues resulting in bluish black discolouration. Hereby a case of ochronosis over the palmar surface of hand in 41-year-old male patient has been reported. Histopathological examination revealed yellowish brown colouration of collagen bundles in reticular dermis over palm of hand.